ASSOCIATION BETWEEN MURINE DOUBLE MINUTE 2 - T309G polymorphism and recurrence of hepatocellular carcinoma after surgical treatment - Uirá Fernandes TEIXEIRA; Andréa Gomes Coelho IZAGUIRRE; Mayara Christ MACHRY; Carlos Thadeu CERSKI; Ajácio Bandeira de Mello BRANDÃO; Paulo Roberto Ott FONTES (Arquivos de Gastroenterologia, 2015)
Background - Discovery and incorporation of biomarker panels to cancer studies enabled the understanding of genetic variation and its interference in carcinogenesis at molecular level. The potential association between single nucleotide polymorphism (SNP) 309 and increased development of tumors, such as hepatocellular carcinoma, has been subject to several studies. This is the first study on this association conducted in Brazil. Methods - 62 cases of cirrhotic patients with hepatocellular carcinoma surgically treated by partial hepatectomy (HPT) or by liver transplantation (LTX) from 2000 to 2009 at Santa Casa Hospital Complex, in the city of Porto Alegre, were retrospectively analyzed. Tumor samples from surgical specimen were collected and prepared for study in paraffin blocks. Results - Overall survival was 26.7 months in the HPT group and 62.4 months in the LTX group (P <0.01). Overall tumor recurrence was 66.7% in the HPT group (10/15) and 17% in the LTX group (8/47) (X²=13.602, P <0.01). Alpha-fetoprotein levels >200ng/mL, microvascular invasion and histological grade were associated with tumor recurrence (P <0.01). Recurrence rates in each surgical group and analysis of factors associated with tumor recurrence, when stratified for each genotypic pattern, were both not statistically significant. Conclusion - G/G genotype was not associated with tumor recurrence after surgical treatment and it did not show any correlation with other prognostic factors.